1996
DOI: 10.1109/72.478400
|View full text |Cite
|
Sign up to set email alerts
|

Analog electronic cochlea design using multiplexing switched-capacitor circuits

Abstract: A new design methodology is proposed to realize a real cochlea using the multiplexing switched-capacitor circuits. The proposed technique is based upon the transmission-line model proposed by Zwislocki (1950). At the cost of the increase in the number of clock phases, the decay rate in the transition region of the filter section can be increased by adding only a few components. Therefore, the components and chip area of the designed silicon cochlea can be small. An experimental chip containing four filter sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A number of electronic circuits cochlear models have been designed with strong emphases on their applications to cochlear implants [17][18][19][20][21][22][23][24][25][26]. In addition, it has been shown that ergodic sequential logic (SL) biomimetic models are much more hardware-efficient (e.g., consume fewer circuit elements and lower power) compared to standard ordinary differential equation (ODE) biomimetic models [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…A number of electronic circuits cochlear models have been designed with strong emphases on their applications to cochlear implants [17][18][19][20][21][22][23][24][25][26]. In addition, it has been shown that ergodic sequential logic (SL) biomimetic models are much more hardware-efficient (e.g., consume fewer circuit elements and lower power) compared to standard ordinary differential equation (ODE) biomimetic models [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%